Virtual Canadian Realities: Charting the Scott Pilgrim Universe - Murphy, David (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2012)
Through a mixture of political-economic and textual analysis, this article examines the Scott Pilgrim franchise, consisting of a series of graphic novels, feature film, and video game, from a transmedia storytelling perspective. By doing so, the author insists that the franchise constructs a globally networked vision of English-Canadian identity through a selective representation of Toronto that situates the city as a cultural filter for globally produced media. While arguing that transmedia storytelling presents a highly fractured fictional universe, with each form of media adding an additional layer of interpretation, the article calls attention to how the Scott Pilgrim franchise utilizes a narrative strategy commonly referred to as “magical realism,” which in the case of transmedia storytelling is perhaps better understood as a form of “virtual realism.” From this perspective, while admitting that the Scott Pilgrim fictional universe exhibits Canadian concerns over the role technologies play in the construction of identity, the author insists that the franchise also draws upon a broader internationally networked nostalgia for classic video games.